Set design as 21st century art - Łarionow, Dominika (Ars inspiratio: Studies dedicated to Professor Eleonora Jedlińska, 2024)
Over the past hundred years, there has been a migration of the concept of decoration from the theater, where it formed the background of performances, to contemporary art galleries, where it shapes the composition of exhibition spaces. This process has become important for the Author of this article, asking, among other things, about the place of the achievements of artists who daily practice the profession of theater set design in the research interests of such fields as art history, among others. The article also includes a consideration of the history of stage design, as well as a discussion of avant-garde theories devoted to the field. Nowadays, stage design has ceased to be just a servant decoration, in the 21st century it has become an autonomous art, which is aggressively present in ever wider contexts.